2021
DOI: 10.3390/fi13050116
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Mobile-Assisted Formative Assessment to Promote Students’ Self-Determination

Abstract: Motivation is an important issue to consider when designing learning activities, including mobile learning and assessment. While previous research provides evidence for the motivational impact of mobile learning, not many pedagogical frameworks exist for the design of mobile-assisted learning and assessment. The current study is grounded in the Self-Determination Theory of motivation and proposes a pedagogical framework for mobile-assisted formative assessment, aiming at enhancing student motivation. For a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 67 publications
3
18
0
1
Order By: Relevance
“…This means that, based on this sample, there is significant difference between student motivation and the implementation of technology integrated formative assessment strategies. The results are in line with previous studies about technology-supported assessments where students were more favorable towards technology integrated instruction compared to those who used paper-based assessments [49].…”
Section: Discussionsupporting
confidence: 91%
“…This means that, based on this sample, there is significant difference between student motivation and the implementation of technology integrated formative assessment strategies. The results are in line with previous studies about technology-supported assessments where students were more favorable towards technology integrated instruction compared to those who used paper-based assessments [49].…”
Section: Discussionsupporting
confidence: 91%
“…Similar research findings are documented in published works [20,21]. Gezer et al (2021) found that FA procedures in eighth-grade mathematics significantly improved [22] students' attitudes toward mathematics. The experimental group of students developed a positive attitude toward mathematics, according to this study.…”
Section: The Relationship Between Fa and Students' Attitudessupporting
confidence: 87%
“…The experimental group of students developed a positive attitude toward mathematics, according to this study. Nikou (2021) discovered that mobile learning assisted formative evaluation significantly increased the motivation and attitudes of fifth-year secondary school students toward learning in local culture class in a comparable experimental study [23]. According to Ozan and Kincal (2018), FA improved students' attitudes toward learning by emphasizing the importance of helping students understand their learning levels.…”
Section: The Relationship Between Fa and Students' Attitudesmentioning
confidence: 99%
“…Diversos autores coinciden en las ventajas que proporciona el aprendizaje mediado por Smartphones entre las que destaca la posibilidad de acceder e interactuar en el medio digital en diversos contextos generando nuevas formas de aprendizaje e investigación, pero sin olvidar en ningún momento que el papel del profesorado en este cometido es fundamental, ya que debe diseñar y desarrollar experiencias de aprendizaje significativas (Baccari et al, 2016;Hinojo et al, 2020;Kukulska-Hulme et al, 2009;Nikou y Economides, 2021;Sharples et al, 2009).…”
Section: Introductionunclassified